First synthesis of (±)-myristicyclin A. Issue 11 (2nd November 2018) - Kubo, Shinichiro; Mori, Naoki; Watanabe, Hidenori; Takikawa, Hirosato
ABSTRACT: The first synthesis of myristicyclin A, which was isolated from the Papua New Guinean plant Horsfieldia spicata, is described. The synthesis features acid-mediated hydroarylation reaction to form a dihydrocoumarin moiety, construction of the 2, 8-dioxabicyclo[3.3.1]nonane skeleton under acidic conditions, and regioselective Friedel-Crafts acylation at a later stage. Graphical abstract: : The first synthesis of (±)-myristicyclin A (1 ) was accomplished in eight steps and overall 18% yield.